Early modern architecture and whiteness
1 online resource.
Keywords: "Framing whiteness as a sensorial quality connate with ethical, aesthetic, epistemological, and ontological hierarchies, this edited volume examines how the category of whiteness shaped architectural theories and practices across the early modern period. What was architecture's role in race-making, constructions of whiteness, and processes of othering more generally? How was whiteness architecturally questioned, reinforced, conceptualized, practiced, and materialized? And how did whiteness intersect with categories such as class, nation, gender, beauty, hygiene, and health? In examining these questions, this volume explores the ways premodern critical race studies allow us to reimagine the boundaries and possibilities of architectural research, design, and practice. The book will be of interest to scholars working in architectural history, art history, early modern studies, and the history of race"--